High voltage-gain full-bridge cascaded dc-dc converter for photovoltaic application - Wang, Long; Hossain, Mohammad Zakir; Selvaraj, Jeyraj; Rahim, Nasrudin Abd (Public Library of Science, 2018)
Over the past few years, high step-up dc-dc converters have been drawn substantial attention because of their wide-ranging application not only in the renewable energy sector but also in many other applications. To acquire a high voltage gain in photovoltaic (PV) and other renewable energy applications, a high step-up dc-dc converter is proposed in this paper. The proposed converter structure consists of a full-bridge (FB) module along with an input boost inductor and a voltage multiplier based on the Cockcroft-Walton (CW) principle with a parallel inductor. The key features of the proposed converter are: 1) high voltage gain with lower voltage stress on the switches, diodes and other passive elements without affecting the number of cascaded stages, 2) a minimum size of boost inductance and cascaded stage capacitance that ensures its compactness and low cost, and 3) a minimal number of major components. Circuit operation, steady-state analysis and various design parameters of the proposed converter are explained in details. In order to prove the performance of the theoretical analysis, a laboratory prototype is also implemented. The peak voltage gain and the maximum efficiency obtained are 11.9 and 94.6% respectively with very low input current ripple and output voltage ripple generated.